Digital Brainstorming with Mentimeter: Enlightening Students’ Paragraph Writing - Nurul Puspita (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Mentimeter is a digital brainstorming device to enlarge students’ skill in writing opinion paragraph. This research aims to explore the implementation of this device in students’ brainstorming sessions particularly in creating and establishing ideas through pre-writing stage. Therefore, this research also portrays the students’ engagement improvement that caused on their clarity and structure of the writing. Devoting a qualitative research design, data were gathered across observation and documentation from third-semester students of the English Education study program at Uin Raden Intan Lampung. The results expose that Mentimeter meaningfully improved students’ motivation and engagement during brainstorming sessions. Its collaborative and visual features stimulated students to promote ideas more easily and comprehensiveness, which in turn helped them form more focused and comprehensible paragraphs. Students’ writings established clearer topic sentences, well-developed supporting sentences, and enhanced logical flow, signifying that Mentimeter effectively helped idea generation and organization. Although the results are inspiring, the research declares its restrictions in terms of the opportunity of the classroom and its main focus on organization and content, which delays grammar, vocabulary, and stylistic less examined. In brief, the researcher concludes that incorporating digitals device such as Mentimeter in writing classes may efficiently promote students in incapacitating barriers in the pre-writing phase and recommend further research to expand its long-term impact and implementation among different writing genres.